Indian livestock: Status, characterization and its documentation - N K Verma, (Journal of Livestock Biodiversity, 2025)
Livestock sector is an integral part of Indian agricultural system. In this review, present status of population, characterization and documentation of Indian livestock with special emphasis on indigenous has been given.